DISKURSUS TAX AMNESTY MELALUI RUU PENGAMPUNAN NASIONAL (Potencial Fraud and Money Laundering Perspective) - Hanif Yusuf Seputro; Yuyung Rizka Aneswari; I. Nyoman Darmayasa (JAFFA, 2016)
Objective of this study is to explore discourse and issues on tax amnesty, and give several feedbacks for improvement of implementation of tax amnesty.  This study employs descriptive method.  First finding of this study signify that the tax amnesty becomes one of options of the central government to achieve target of tax sector.  Second, Indonesia should learn from failure and success on implementation of tax amnesty in the prior period.  Third, RUU (draft of law) of national amnesty must be clear.  The amnesty is specific for tax.  Hence, there will be no possibility to do corruption (TIPIKOR), or even money laundry that use to be done after the corruption (TIPIKOR) is occurred.  Fourth, implementation of the tax amnesty programme should be followed by supporting policies, such as law of (UU) banking confidentiality and so on.  Fifth, tax amnesty is a policy that is expected by many parties to fix their SPT and make confession about their real tax; henceforth they will be more compliant on tax in the future.  Contribution of this study is to give positive discourse that can be used by the central government as feedback on tax amnesty policy as embodied in RUU national amnesty.